Altered Intestinal Permeability Biomarkers in Schizophrenia: A Possible Link with Subclinical Inflammation. Issue 2 (April 2022) - Gokulakrishnan, Kuppan; Nikhil, Joyappa; VS, Sreeraj; Holla, Bharath; Thirumoorthy, Chinnasamy; Sandhya, Narasimhan; Nichenametla, Sonika; Pathak, Harsh; Shivakumar, Venkataram; Debnath, Monojit; Venkatasubramanian, Ganesan; Varambally, Shivarama
Background and Purpose: Emerging studies have shown that gut-derived endotoxins might play a role in intestinal and systemic inflammation. Although the significance of intestinal permeability in modulating the pathogenesis of Schizophrenia (SCZ) is recognized, not much data on the specific role of intestinal permeability biomarkers, viz., zonulin, lipopolysaccharide-binding protein (LBP), and intestinal alkaline phosphatase (IAP) in SCZ is available. Therefore, we measured the plasma levels of zonulin, LBP, and IAP and its correlation with neutrophil-to-lymphocyte ratio (NLR); a marker of systemic inflammation in patients with SCZ. Methods: We recruited 60 individuals, patients with SCZ ( n = 40) and healthy controls ( n = 20), from a large tertiary neuropsychiatry center. Plasma levels of zonulin, IAP, and LBP were quantified by enzyme-linked immunosorbent assay. Results: Plasma levels of both LBP and zonulin were significantly increased ( P <0.05), whereas the IAP levels ( P <0.05) were significantly decreased in patients with SCZ compared to healthy controls. Pearson correlation analysis revealed that zonulin and LBP had a significant positive correlation with NLR, and IAP negatively correlated with NLR. Individuals with SCZ had higher independent odds of zonulin [odds ratio (OR): 10.32, 95% CI: 1.85–57.12], LBP [OR: 1.039, 95% CI: 1.02–1.07], and IAP [OR: 0.643, 95% CI: 0.471–0.879], even after adjusting for potential confounders. Conclusion: Our study demonstrates an association of zonulin, LBP, and IAP in Asian Indian SCZ patients and correlates with NLR. Our results indicate that low-grade inflammation induced by metabolic endotoxemia might be implicated in the pathoetiology of SCZ.